Chronic Pelvic Pain and Sexual Dysfunction Among Females and Males Receiving Treatment for Opioid Use Disorder - Reichmann, Geetika; Parlier-Ahmad, Anna Beth; Beck, Lori; Thakkar, Bhushan; Alappattu, Meryl; Boissoneault, Jeff; Martin, Caitlin E. (Frontiers in Pain Research, 2022)
Introduction: Chronic pain brings complexity to opioid use disorder (OUD). Psychosocial and neurobiological risks for Chronic Pelvic Pain (CPP) and OUD overlap. The primary objective of this exploratory study is to compare sex-specific prevalence of CPP and sexual dysfunction between individuals receiving buprenorphine for OUD and a comparison group receiving treatment for other chronic medical conditions (CMC). Methods: Participants from an OUD treatment (n = 154) and primary care clinic (n = 109) completed a survey between July 2019 and February 2020 assessing reproductive and sexual health. Sex-stratified CPP and pain interference measures were adapted from the Brief Pain Inventory for females, and for males, the Brief Male Sexual Function Inventory and NIH Chronic Prostatitis Symptom Index. The Male and Female Sexual Function Index assessed sexual dysfunction. Prevalence of CPP and sexual dysfunction between groups were compared using Pearson χ2 and Fisher's Exact tests. Results: Participants were 54.4% female and 75.0% Black with almost half having a psychiatric diagnosis. Among OUD females, the highest pain severity reported was for menstrual-related pain, and for OUD males, testicular pain. CPP most interfered with mood in OUD females vs. sleep and enjoyment of life in OUD males. There were no differences in prevalence for global sexual dysfunction with 91.6% of females and 84.2% of males screening positive across groups. Discussion/Implications: CPP and sexual dysfunction are important components of wellness and may play a role in OUD recovery trajectories. The value of addressing CPP and sexual dysfunction in tailored comprehensive, sex-informed OUD treatment approaches should be further investigated.